Intra-cultural and Inter-cultural Contact Orientation of International Students in Japan: Uncertainty Management by Cultural Identification - Taniguchi, Norihito; Takai, Jiro; Skowronski, Dariusz (Journal of International Students, 2022)
In this study, we examined this issue by focusing on how international students in Japan perceive cultural contact with their host and home culture members during their sojourn. We applied a qualitative approach based on grounded theory, collecting data through semi-structured interviews with 41 international students from China, the United Kingdom, and the United States. According to the social identity and anxiety/uncertainty management approach, we interpreted the findings on how international students manage uncertainty in the Japanese environment by identifying with the host and their own home cultures for their psychological well-being, which we distinguished as intercultural or intracultural contact orientation. International students demonstrated an intracultural rather than intercultural contact orientation due to the host nationals reacting to them as “foreigners".